Bone disease in early detected Gaucher Type I disease: A case report. Issue 5 (26th June 2022) - Gragnaniello, Vincenza; Burlina, Alessandro P.; Manara, Renzo; Cazzorla, Chiara; Rubert, Laura; Gueraldi, Daniela; Toniolli, Ermanno; Quaia, Emilio; Burlina, Alberto B.
Abstract: Gaucher disease (GD) is a lysosomal disorder characterized by the storage of glucosylceramide in macrophages ("Gaucher cells"), particularly in the spleen, liver, and bone marrow. The most common phenotype, GD type 1, usually presents with hepatosplenomegaly, cytopenias, and sometimes bone involvement at variable age. Enzyme replacement therapy (ERT) is available and effective, but some severe manifestations are irreversible (e.g., osteonecrosis), so that early treatment is crucial. We describe a 4‐year‐old Albanian male with GD type 1, diagnosed through newborn screening (NBS), presented during follow up with multiple osteonecrotic areas in both femurs. He had no other symptoms or signs of disease, except for increasing of lyso‐Gb1 biomarker. Early initiation of ERT allowed a partial improvement of bone lesions. Our case highlights the importance of NBS for GD and of close follow‐up of presymptomatic patients, especially if biomarker levels are increasing. In the absence of NBS, GD should be considered in patients who present with bone lesions, also isolated. Early diagnosis and treatment improve the course of disease and avoid irreversible sequelae.